2001
DOI: 10.1097/00004347-200107000-00007
|View full text |Cite
|
Sign up to set email alerts
|

k-ras Mutation May Be an Early Event in Mucinous Ovarian Tumorigenesis

Abstract: We explored the possible pathogenetic pathway for mucinous ovarian tumorigenesis by examining the k-ras mutational patterns in ovarian mucinous tumors (OMTs) with benign, borderline, and invasive epithelium in which the different types of mucinous epithelium are in close proximity. Sixteen patients with ovarian mucinous borderline tumors (OMBTs) and 4 patients with grade 1 ovarian mucinous adenocarcinomas (OMCs) were selected for the presence of a single histologic section which contained a clear "transition" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 17 publications
4
40
0
2
Order By: Relevance
“…They also found 23% LOH rate in 6q27, which was significantly lower than 53% identified in serous cancer (22). High K-RAS mutation rates were also found in mucinous borderline and invasive ovarian carcinomas (23,24). Ikeda et al (25) and Wertheim et al (26) identified one of seven and two of five mucinous ovarian carcinomas, respectively, with TP53 mutation.…”
Section: Discussionmentioning
confidence: 91%
“…They also found 23% LOH rate in 6q27, which was significantly lower than 53% identified in serous cancer (22). High K-RAS mutation rates were also found in mucinous borderline and invasive ovarian carcinomas (23,24). Ikeda et al (25) and Wertheim et al (26) identified one of seven and two of five mucinous ovarian carcinomas, respectively, with TP53 mutation.…”
Section: Discussionmentioning
confidence: 91%
“…Most studies have shown a high and increasing frequency of KRAS mutations in mucinous cystadenomas, borderline tumors and carcinomas, ranging from 33 to 86%. 47,70,72,75,87,88 Several groups 75,87,88 have noted similar KRAS mutation patterns in benign, borderline and malignant mucinous areas within the same neoplasm, which suggests that KRAS mutation is an early event in mucinous tumorigenesis. It has also been noted that the rate of TP53 mutations is lower in mucinous borderline tumors than mucinous carcinomas (13 vs 40%).…”
Section: Molecular Genetic Datamentioning
confidence: 99%
“…Further studies have shown similar molecular alterations in all mucinous ovarian tumor types. For example, identical K-ras mutations are frequently found in coexisting borderline and invasive epithelia within a mucinous tumor (16). More importantly, these mutations are not related to the stage of the disease in mucinous tumors, unlike nonmucinous tumors, suggesting a continuum in the development of this cancer (17)(18)(19)(20).…”
mentioning
confidence: 99%